2014
DOI: 10.1159/000358365
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Reactive Oxygen Species Scavenger Enzymes Is Associated with a Good Prognosis in Triple-Negative Breast Cancer

Abstract: Objective: The aim of this study was to investigate the expression of redox proteins in triple-negative breast cancer (TNBC), a breast cancer type which harbors an aggressive phenotype, and to demonstrate the relationships between the expression of reactive oxygen species (ROS) markers and clinical outcome. Methods: From 2000 to 2005, we analyzed tissue samples from 135 cases of TNBC obtained from curative surgeries at the Severance Hospital, Seoul, South Korea. Immunochemical staining for redox proteins was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…These findings suggest that after NF-κB inhibition, these cells may activate a late compensatory pathway that restores the antioxidant capacity. Thus, there may be some compensatory mechanism in cells that triggers increased thiol production likely to contain stress, which is in accordance with the findings of Kim et al [ 57 ], who reported that increased expression of enzyme scavengers is associated with a better prognosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings suggest that after NF-κB inhibition, these cells may activate a late compensatory pathway that restores the antioxidant capacity. Thus, there may be some compensatory mechanism in cells that triggers increased thiol production likely to contain stress, which is in accordance with the findings of Kim et al [ 57 ], who reported that increased expression of enzyme scavengers is associated with a better prognosis.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the lack of a known potent signaling pathway to deal properly with redox variations [ 50 , 51 ], NF-κB-silenced MDA-MB-231 exhibited important components of the antioxidant arm of the redox balance in the microarray analysis, such as glutathione peroxidase (GPX2), glutathione transferases (GSTM1, GSTK1, GSTP1, GSTT1 and GSTT2), ceruloplasmin (CP) and selenoprotein (SEPW1) ( Table 2 ). Overexpression of ROS scavenger enzymes in TNBC has been associated with a good prognosis [ 57 ]. NF-κB inhibition for 48 h restored the thiol content and equilibrated the differences in the lipid peroxidation profile observed between the treated sample and its control, although the treated group retained elevated peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Basal-like TNBC cells were reported to be highly sensitive to the mTOR inhibitor everolimus, whereas a subgroup of TNBC cells, comprising lines characterized as stem-like cancer cells, are less sensitive to this drug 24 . Given that the cellular redox state affects the regulation of signal transduction pathways and the development of drug resistance, this could be used to dictate therapeutic strategies for TNBC 25 . Many studies have shown that redox mechanisms regulate mTORC1 activity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione and glutathione-dependent enzymes (such as glutathione peroxidase, glutathione S-transferase (GST) and glutathione reductase) are involved in cell defense against ROS [8][9][10][11]. Many reports indicate the development of oxidative stress in cancer patients [12][13][14][15]. However, there is not much research regarding the level of oxidative stress during the treatment.…”
Section: Introductionmentioning
confidence: 99%